RELIGIUSITAS DALAM NOVEL SASTRA INDONESIA: STUDI KASUS KHOTBAH DI ATAS BUKIT KARYA KUNTOWIJOYO - Erli Yetty (Sawo Manila, 2010)
A research of religiosity in a literature up to now tends to develop. Whetherthe faith in God or the life of religiosity discovered in the structure of a novelKhotbah di Atas Bukit become very crucial. By using structural approach,therefore, there will be such intrinsic meaning in the novel and the connectionbetween the novel and the world around will be verified. In the novel, religiousvalues are proven by sharp criticism and satire. The author also describesabout the unharmonious life with the norm in religion and also the demand ofcultured societies.